Revolutionizing Accounting through Digital Transformation: The Impact of Technology - Surya, Bernadeth Trisha Marvellyn (Engineering Science Letter, 2024)
This research paper delves into the transformative impact of digital technologies on the accounting industry, emphasizing the imperative for adaptation in the face of global organizational digitization. Examining the intricate consequences of digital transformation on accounting processes, the study addresses challenges, prospects, and shifts in perspective resulting from technological integration. Employing a questionnaire as the primary data-gathering tool, opinions were solicited from a diverse sample of 120 institutions spanning industries such as communications, insurance, food, and cleaning materials. Utilizing the Rensis Likert five-point rating system, responses were collected from 237 participants out of the 320 electronic questionnaires distributed via email. The findings underscore the necessity of a comprehensive strategy encompassing skill development, technology adoption, cultural change, and proactive engagement with regulatory and technological advances. This approach is essential for successfully navigating the evolving landscape of digital transformations in the accounting industry. Implementing these recommendations positions accountants, companies, and legislators to thrive in the progressively digital financial environment.